2022
DOI: 10.3389/fphar.2021.806829
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin From Dioscorea Nipponica Rhizoma Against Graves’ Disease—On Network Pharmacology and Experimental Evaluation

Abstract: Dioscorea nipponica rhizoma (DNR) is commonly used for the cure of hyperthyroidism resulting from Graves’ disease (GD) or thyroid nodules. However, its therapeutic mechanism remains unclear. This study aimed to utilize network pharmacology integrated molecular docking and experimental verification to reveal the potential pharmacological mechanism of DNR against GD. First, the active componds of DNR were collected from the HERB database and a literature search was conducted. Then, according to multisource datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Then, the putative targets of D7 mapped to the inflammatory osteolysis-related targets to acquire overlapping targets. A Venn diagram was obtained with the Venn diagram website ( http://bioinformatics.psb.ugent.be/webtools/Venn/ ) [ 26 ] to identify the intersection of D7 and inflammatory osteolysis [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, the putative targets of D7 mapped to the inflammatory osteolysis-related targets to acquire overlapping targets. A Venn diagram was obtained with the Venn diagram website ( http://bioinformatics.psb.ugent.be/webtools/Venn/ ) [ 26 ] to identify the intersection of D7 and inflammatory osteolysis [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Dio has demonstrated inhibitory effects on the activation and phosphorylation of Rap1-mitogen-activated extracellular signal-regulated kinase (MEK) and PI3K-AKT signaling pathways and promoted cell apoptosis and GD remission. In terms of phosphorylation deactivation in IGF-1R, Dio promoted Nthy-ori three to one cells (normal thyroid cells) apoptosis in vitro and relieved GD in rats ( Xin et al, 2021 ).…”
Section: Tcm and Other Treatmentsmentioning
confidence: 99%
“…Studies have reported that TSAb can regulate the proliferation activity of thyroid cells via the PI3K/AKT pathway ( 10 , 11 ). Chinese medicine for hyperthyroidism primarily modulates the proliferation and apoptosis of thyroid cells through regulation of the PI3K/AKT pathway to effectively treat GD ( 12 - 14 ). Furthermore, certain studies suggest that AKT can interact with heat shock protein (HSP) to exert diverse influences on cell signaling mechanisms.…”
Section: Introductionmentioning
confidence: 99%